2017
DOI: 10.1371/journal.pone.0175367
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic alpha 7 receptor expression and modulation of the lung epithelial response to lipopolysaccharide

Abstract: Nicotine modulates multiple inflammatory responses in the lung through the nicotinic acetylcholine receptor subtype alpha7 (α7). Previously we reported that α7 modulates both the hematopoietic and epithelium responses in the lung to the bacterial inflammogen, lipopolysaccharide (LPS). Here we apply immunohistochemistry, flow cytometry and RNA-Seq analysis of isolated distal lung epithelium to further define α7-expression and function in this tissue. Mouse lines were used that co-express a bicistronic tau-green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 84 publications
(151 reference statements)
6
66
1
Order By: Relevance
“…These cells were able to migrate from the blood following LPS challenge 52 . Contrasting to previous studies 49 , we found that only a small fraction of interstitial macrophages but not alveolar macrophages expressed α7nAChR in normal conditions. Meanwhile, a study by Mikulski W et.al showed that no α7nAChR mRNA expression was observed in bronchoalveolar lavage cells 53 , and we did not observe either.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These cells were able to migrate from the blood following LPS challenge 52 . Contrasting to previous studies 49 , we found that only a small fraction of interstitial macrophages but not alveolar macrophages expressed α7nAChR in normal conditions. Meanwhile, a study by Mikulski W et.al showed that no α7nAChR mRNA expression was observed in bronchoalveolar lavage cells 53 , and we did not observe either.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown the infiltration of M1 type macrophage was enhanced in adipose tissue in α7nAChR knockout mice 48 . Literature shows that approximately 20% of CD45 + cells expressed α7nAChR in the lung 49 . In contrast to CD45 + , CD11b + , CD8 + and B220 + cells, F4/80 + , Gr1 + and CD11c + cells exhibited different expression levels of α7nAChR 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This also means that the nicotine-α7 interaction imparts several parallel and potentially very different effects depending upon the target tissues and cells as well as the challenging agent (inflammagen). In the lung the cell specific expression of α7 includes neuronal cells (e.g., autonomic nervous system) as well as non-neuronal cells (including alveolar macrophages (AM), club cells and Type II alveolar cells [ 7 ]). The anti-inflammatory impact role of α7 has been best characterized in terms of the response to inflammagens such as lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…In this case α7 tends to suppress the inflammatory responses acting through the vagal nerve as well as directly inhibiting macrophage pro-inflammatory NF-κB signaling and activation of cytokine cascades (e.g., TNFα; [ 2 , 3 , 8 ]). Additionally, effects by α7 on lung epithelial cells include modifying their response to LPS [ 7 ] through alterations to subsequent signaling processes leading to recruitment and infiltration of bone marrow cells into the lung as well as changes to local production of certain mucins (e.g., Muc5b), surfactant proteins and genes of fibrosis. An important issue that has been raised by these studies is what role does α7 have in modulating inflammatory processes in response to CS and whether or not these are distinct from those activated by LPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation